Coating of Li1+x[Ni0.85Co0.10Mn0.05]1−xO2 Cathode Active Material with Gaseous BF3. Issue 12 (6th August 2020) - Eisele, Lea; Skrotzki, Julian; Schneider, Marius; Bolli, Christoph; Erk, Christoph; Ludwig, Thilo; Schaub, Anke; Novák, Petr; Krossing, Ingo
Abstract : Ni-rich cathode active material Li1+x [Ni0.85 Co0.10 Mn0.05 ]1−x O2 (NCM851005) was exposed to BF3 gas at room temperature with pressures between 25 mbar and 2478 mbar. It mainly gave an LiBF4 coating by reaction with the basic surface lithium impurities. The electrochemical investigations up to full-cell level displayed a significantly improved long-term cycling behavior at 45 °C for only 0.08 wt% BF3 coated NCM851005 material, compared to pristine NCM851005 material. The internal resistance of full-cells was reduced for all tested amounts of BF3 coating (after 300 cycles: pristine NCM851005 +293% and 0.08 wt% BF3 coated NCM851005 +133% resistance built-up). Moreover, online electrochemical mass spectrometry studies showed a reduced CO2 release in the first cycle of half-cells built with the coated NCM851005 material compared to those with pristine NCM851005 material. The thermal annealing of the coated NCM851005 material at 200 °C or 400 °C led to a decrease of LiBF4, but to an increase of LiF content on the surface. However, coated NCM851005 material with thermal annealing exhibits lower discharge capacities after 250 cycles compared to NCM851005 material with equal coating amount, which were not thermally annealed.